2023
DOI: 10.1002/anie.202216309
|View full text |Cite
|
Sign up to set email alerts
|

Designed Iron Catalysts for Allylic C−H Functionalization of Propylene and Simple Olefins

Abstract: Propylene gas is produced worldwide by steam cracking on million-metric-ton scale per year. It serves as a valuable starting material for π-bond functionalization but is rarely applied in transition metal-catalyzed allylic CÀ H functionalization for fine chemical synthesis. Herein, we report that a newly-developed cationic cyclopentadienyliron dicarbonyl complex allows for the conversion of propylene to its allylic CÀ C bond coupling products under catalytic conditions. This approach was also found applicable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 117 publications
2
66
0
Order By: Relevance
“…Our group has previously demonstrated that cyclo­penta­dienyl­iron(II) dicarbonyl complexes are capable of coordinating to and enhancing the C–H acidity of a range of unsaturated substrates, to facilitate the removal of protons at the allylic, propargylic, or allenic positions . As a result, functional group-tolerant amine and pyridine bases could be used for abstraction of the α-proton to deliver a nucleophilic organoiron species that could undergo subsequent electrophilic functionalization with predictable S E 2′ selectivity.…”
mentioning
confidence: 99%
“…Our group has previously demonstrated that cyclo­penta­dienyl­iron(II) dicarbonyl complexes are capable of coordinating to and enhancing the C–H acidity of a range of unsaturated substrates, to facilitate the removal of protons at the allylic, propargylic, or allenic positions . As a result, functional group-tolerant amine and pyridine bases could be used for abstraction of the α-proton to deliver a nucleophilic organoiron species that could undergo subsequent electrophilic functionalization with predictable S E 2′ selectivity.…”
mentioning
confidence: 99%
“…[ 50,51 ] In addition, the strong electron‐withdrawing cyano groups in K‐CN‐PHI also caused an enhanced electron paramagnetic resonance (EPR) signal (Figure 1d), revealing a much higher number of unpaired electrons within the π ‐conjugated structure. [ 52 ] The rearranged electronic structure make K‐CN‐PHI exhibits an obviously different micromorphology feature, as confirmed by scanning electron microscope (SEM) and transmission electron microscope (TEM) (Figure S4, Supporting Information). Compared with PCN, which featured an irregular and multilayered structure (Figure S4a,c, Supporting Information), K‐CN‐PHI showed multiple separated sheets with a smaller particle size (Figure S4b,d, Supporting Information) and thereafter a higher Brunauer−Emmett−Teller (BET) surface area (93.50 m 2 g −1 , 5.9 times higher than PCN) (Figure S1c,d, Supporting information).…”
Section: Resultsmentioning
confidence: 87%
“…For K‐CN‐PHI, in addition to the electron transition of π → π * below 450 nm in the conjugated aromatic system, an additional absorption band in the region of 450–600 nm, which could be ascribed to the transition of n→ π * induced by lone‐pair electrons at N‐defect sites (C≡N), was observed. [ 52,54 ] The band structure of K‐CN‐PHI was also adjusted, with a slightly increased bandgap ( E g ) that is caused by the quantum confinement effect owing to the decreased interlayer distance (insert in Figure 2a). [ 55 ] Valence band (VB)‐XPS analysis (Figure 2b) revealed VB potentials ( E VB ) of 1.51 and 1.73 V (vs a normal hydrogen electrode [NHE], based on the formula in Supporting Information) for PCN and K‐CN‐PHI, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we suggest that the Grimme empirical D3 dispersion corrections (Becke‐Johnson‐damping or zero‐damping) [90,91] to be added when using functionals with poorly described noncovalent interactions such as B3LYP. For single‐point calculations, the Minnesota functionals such as M06 have become popular, and have been extensively used in transition metal catalyst systems (not limited to the current review paper) [92–97] . The PBE0 functional also performs well in describing metal‐catalysed systems, and is reliable in both geometry optimization and single‐point energy calculations while balancing computational accuracy and elapsed time.…”
Section: Discussionmentioning
confidence: 99%
“…For single-point calculations, the Minnesota functionals such as M06 have become popular, and have been extensively used in transition metal catalyst systems (not limited to the current review paper). [92][93][94][95][96][97] The PBE0 functional also performs well in describing metalcatalysed systems, and is reliable in both geometry optimization and single-point energy calculations while balancing computational accuracy and elapsed time. In addition, the double hybridization functionals such as ωB97X-V or ωB97M-V can bring higher accuracy when computational resources allow.…”
Section: Discussionmentioning
confidence: 99%